Web-Based E-Business Application with Customer Data Encryption Feature to Protect Privacy at CV Jasa Karya Rizki - Siregar, Lola Kamal; Ikhwan, Ali (The IJICS (International Journal of Informatics and Computer Science), 2025)
This research presents the development of a web-based e-business application integrated with a data encryption feature using the Data Encryption Standard (DES) algorithm to protect customer privacy. The system is designed for CV Jasa Karya Rizki to manage customer and transaction data securely. DES encryption is implemented manually using PHP without relying on external libraries. The encryption process is applied during data input to ensure that only ciphertext is stored in the database. When data needs to be accessed, decryption is performed on-the-fly, allowing authorized users to view the original information securely. The application consists of core modules for managing customer data, transactions, products, and reports. Encryption and decryption functions are encapsulated within the system's main classes, enhancing maintainability and modularity. Testing results show that the DES implementation functions correctly, providing a secure data management workflow without negatively impacting system performance. This research demonstrates that classic encryption algorithms like DES can still be effectively applied in small-scale business environments to enhance data security and customer trust.